Understanding the knowledge of Mogpog residents about heavy metal pollution due to mining and its associated health risk - Nolos, Ronnel C.; Sevilla-Nastor, Janice B.; Villanueva-Peyraube, Jessica D.; Sobremisana, Marisa J. (Brawijaya University, 2024)
The municipality of Mogpog in the Philippines was one of the severely hit areas during the 1993 mining disaster in the province of Marinduque. After three (3) decades, the aftermath of the disaster still lingers in the municipality and even in the whole province. This study was conducted to assess the relationship between the social demographics of the residents of Mogpog and their knowledge about heavy metal (HM) pollution and its associated health risks. A cross-sectional survey was conducted among the 314 residents of Mogpog. Six (6) social demographics were considered, such as age, sex, marital status, highest education attainment, monthly household income, and whether the respondents were government employees or not. Results of the binomial logistic regression analysis showed that the social demographics affecting the respondents’ knowledge about HM pollution were marital status and monthly household income (significant at the 0.05 level). Married individuals may have larger and more diverse social networks, which could expose them to a wider range of information, including environmental issues. On the other hand, those with lower incomes may have limited access to formal education or information resources, which could result in lower environmental awareness. The results underscore the need for specific interventions and educational initiatives to enhance the understanding of the adverse health impacts associated with HM pollution among residents in Mogpog